2004
DOI: 10.1111/j.1365-2265.2004.02181.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of five‐year growth hormone replacement therapy on muscle strength in elderly hypopituitary patients

Abstract: Elderly patients with adult onset GH deficiency had decreased baseline muscle strength also after correction for age and sex. The 5-year GH replacement therapy normalized knee flexor strength and improved, but did not fully normalize, knee extensor strength and handgrip strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 47 publications
2
44
0
Order By: Relevance
“…After 10 years, BF was reduced, and LBM was increased, as measured using DEXA. This is consistent with the lipolytic and anabolic effects of GH observed in previous studies (4,10,23,24), demonstrating that a moderate dose of GH can induce a sustained improvement in body composition in elderly GHD adults. GH replacement, as previously shown (10,25), had a more marked effect on isometric knee flexor strength than on isokinetic knee flexor strength, possibly as a consequence of more reduced isometric strength in untreated GHD adults (9,26).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…After 10 years, BF was reduced, and LBM was increased, as measured using DEXA. This is consistent with the lipolytic and anabolic effects of GH observed in previous studies (4,10,23,24), demonstrating that a moderate dose of GH can induce a sustained improvement in body composition in elderly GHD adults. GH replacement, as previously shown (10,25), had a more marked effect on isometric knee flexor strength than on isokinetic knee flexor strength, possibly as a consequence of more reduced isometric strength in untreated GHD adults (9,26).…”
Section: Discussionsupporting
confidence: 79%
“…We demonstrated that GHD adults above 60 years of age had decreased age-and sex-adjusted muscle strength (4). The 5 years of GH replacement therapy normalized age-and sex-adjusted values of knee flexor strength, whereas knee extensor and handgrip strength were not fully normalized in the elderly GHD patients (4).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only eight different cohorts of patients were described in these 14 studies, because several studies described data from the same patient cohort. The studies by Götherström et al (12,19) and Toogood et al (20) (nZ12) also described the same patient cohort. Therefore, the data of these studies are described in combination.…”
Section: Resultsmentioning
confidence: 83%